Viabilidade populacional do Muriqui-do-Norte, Brachyteles hypoxanthus (Kuhl,1820) em área fragmentada - Lanna, Andre Monnerat (2015)
The northern muriqui, Brachyteles hypoxanthus, is an endemic primate of the Atlantic Forest. Its historic distribution comprises Minas Gerais, Rio de Janeiro, Espírito Santo and Bahia. The forest destruction resulted in drastic reduction of muriqui’s natural habitat and currently, they are found in only 14 localities. All groups sum about 1,000 individuals. Two of these areas are the municipalities of Santa Maria de Jetibá (SMJ) and Santa Teresa (ST) in the central mountainous region of Espírito Santo, where the groups are isolated from each other or partially connected. Due to isolation, some young females who emigrate often become solitary probably because of the lack of habitat connection with other social groups. We conducted a Population Viability Analyzes (PVA) in the Vortex program to investigate the viability of these social groups. Besides estimating population viability in current conditions, we also did simulations predicting management actions, such as translocations of individuals and reforestation. We found that the muriqui populations (88 muriquis monitored in SMJ and 25 in ST) are vulnerable specially due to the loss of habitat connection between social groups, which reduces the success of migration of young females. When in isolated forest fragments and with greater reduction of reproductive females, the groups of muriquis tend to extinction in just 30 years. In completely isolation, the model predicts the negative growth rate of populations and high probability of extinction in the next 100 years. Due to the proximity of the five groups of muriquis in SMJ, the reforestation between fragments is a promising strategy for increasing population viability. Considering the possibility of young females migration between social groups, the model present a growth trend with the increasing of the SMJ population up to 350 muriquis in about 50 years. However, in ST, the 3,562 ha Biological Reserve Augusto Ruschi, comprises only one known group of muriquis with 25 individuals, 12 of them males. If this group remains in isolation, they will tend to extinction. However, the introduction of young females may increase population viability, for example, by the formation of a second social group. Modeling suggests that the formation of a second group decreases the loss of female migrants, ensuring the growth of the population over the next 100 years. We concluded that the viability of muriquis population depends mostly on the connection between at least two social groups, thus avoiding the loss of migrant young females.